Calein C, a Sesquiterpene Lactone Isolated From Calea Pinnatifida (Asteraceae), Inhibits Mitotic Progression and Induces Apoptosis in MCF-7 Cells - Caldas, Lhaís Araújo; Horvath, Renato O.; Ferreira-Silva, Guilherme Álvaro; Ferreira, Marcelo J. P.; Ionta, Marisa; Sartorelli, Patricia (Frontiers in Pharmacology, 2018)
Breast cancer is the most common cancer in women worldwide. Estrogen receptor-positive (ER+) breast cancer represents approximately 75% of diagnosed cases, while 15- 20% of them are triple-negative (TN). Although there have been improvements in the therapeutic approach, the mortality rate remains elevated. Thus, it is necessary to identify new chemotherapeutic agents. The present study aimed to evaluate the effects of calein C, a sesquiterpene lactone isolated from Calea pinnatifida, on breast cancer cell lines MCF-7 (ER+), Hs578T (TN) and MDA-MB-231 (TN). Calein C significantly reduced the viability of all cell lines; however, MCF-7 cells were more responsive than MDA-MB-231 or Hs578T cells. Thus, the MCF-7 cell line was selected for further investigation. We demonstrated that calein C inhibited cell cycle progression in MCF-7 cells at M-phase. Increased frequency of mitosis was observed in calein C-treated samples compared to the control group, especially of the cell population in initial stages of the mitosis. These events were associated with the ability of calein C to modulate expression levels of critical regulators of mitosis progression. We observed a significant reduction in the relative mRNA abundance of PLK1 and AURKB along with a concomitant increase in CDKN1A (p21) in treated samples. In addition, calein C induced apoptosis in MCF-7 cells due to, at least in part, its ability to reduce the BCL2/BAX ratio. Therefore, our data provide evidence that calein C is an important antimitotic agent and should be considered for further in vivo investigations.